Pelagic effects of offshore wind farm foundations in the stratified North Sea. (August 2017) - Floeter, Jens; van Beusekom, Justus E.E.; Auch, Dominik; Callies, Ulrich; Carpenter, Jeffrey; Dudeck, Tim; Eberle, Sabine; Eckhardt, André; Gloe, Dominik; Hänselmann, Kristin; Hufnagl, Marc; Janßen, Silke; et al.
Highlights: First time bio-physical empirical indication of OWF effects on the pelagic ecosystem. High speed, high-resolution remotely operated vehicle (TRIAXUS ROTV) transects. We provide empirical indication for increased vertical mixing within the OWFs. There was doming of the thermocline and vertical nutrient transport within the OWFs. Submesoscale chlorophyll- a pillars occurred at regular intervals. Abstract: A recent increase in the construction of Offshore Wind Farms (OWFs) has initiated numerous environmental impact assessments and monitoring programs. These focus on sea mammals, seabirds, benthos or demersal fish, but generally ignore any potential effects OWFs may have on the pelagic ecosystem. The only work on the latter has been through modelling analyses, which predict localised impacts like enhanced vertical mixing leading to a decrease in seasonal stratification, as well as shelf-wide changes of tidal amplitudes. Here we provide for the first-time empirical bio-physical data from an OWF. The data were obtained by towing a remotely operated vehicle (TRIAXUS ROTV) through two non-operating OWFs in the summer stratified North Sea. The undulating TRIAXUS transects provided high-resolution CTD data accompanied by oxygen and chlorophyll- a measurements. We provide empirical indication that vertical mixing is increased within the OWFs, leading to a doming of the thermocline and a subsequent transport of nutrients into the surface mixed layer (SML). Nutrients were taken up rapidly because underwater photosynthetically active radiation (PAR) enabled net primary production in the entire water column, especially within submesoscale chlorophyll- a pillars that were observed at regular intervals within the OWF regions. Video Plankton Recorder (VPR) images revealed distinct meroplankton distribution patterns in a copepod-dominated plankton community. Hydroacoustic records did not show any OWF effects on the distribution of pelagic fish. The results of a pre-OWF survey show however, that it is difficult to fully separate the anthropogenic impacts from the natural variability.